Design of Optical Lens Assembly Method Based on Star Point Bonding and Surface Shape Accuracy - Qiuhan Ma; Xiaozeng Xie; Chunlei Yang; Tianshuo Zhang; Chuncheng Lang; Bo Tang (IEEE Access)
With the development of digital optical systems, the industry quality requirements for optical lenses are becoming higher. A design method for optical lens assembly based on star point bonding and a method for surface shape accuracy are proposed in response to the development of digital optical systems and the continuously improving quality requirements of the optical lens industry. The study adopts the three-point support principle to bond optical lenses, thereby optimizing the assembly process of optical lens components. Finite element analysis is conducted on the lens assembly process using computer-aided engineering software to ensure accuracy and reliability of the assembly. In addition, the matching technique is used to analyze the surface shape error of the lens, further improving the control technology of surface shape accuracy. Compared with traditional binding and ring pressing methods, the research method improved assembly accuracy by at least 30%, significantly reducing stress concentration caused by uneven tightening, and effectively avoiding deformation of optical lenses during processing and assembly. In addition, the surface shape accuracy analysis method was about 50% faster than traditional methods. At the same conditions, the calculation error was reduced by an order of magnitude. These improvements not only improve the assembly accuracy and work efficiency of optical lenses, but also provide strong technical support for the production of optical lenses.